Improvement based on standardized work: an implementation case study - Fin, Julio Cesar; Vidor, Gabriel; Cecconello, Ivandro; Machado, Vanessa de Campos (Brazilian Journal of Operations & Production Management, 2017)
Standardized work is an effective way for process improvement, specially when it is applied to manual tasks such as assembly lines. This tool is part of Toyota Production System and based on wastes reduction. Thus, the objectives were to implement standardized work in a medium chassis assembly line and measure the benefis from optimization of operators’ tasks and movement through waste reduction. In order to achieve these results, a single case study was performed in a medium chassis assembly line that is part of a company in South Brazil. The steps involved: defining the object of study; time measurement and takt time definition; creating a production capacity sheet; defining the minimum number of operators and balancing the line; determining minimum work in process; defining the new layout; creating a standardized operations sheet and a standardized operations routine sheet; training and implementing standardized work; and verifying the results. Results show 36 minutes reduction in terms of assembly time and 200 meters reduction in terms of operators’ movement on average. Other contributions regard the 9.6% reduction in terms of the assembly line downtime.